Effects of bitter gourd (Momordica Charantia L.) aqueous extract on pathophysiological changes associated with streptozotocin-induced diabetes mellitus type II in neonatal rats - Abdollahi, Maryam (2010)
The aim of the current research was to determine the effects of Momordica charantia (MC) whole fruit aqueous extract on pancreatic, hepatic, and renal histopathological changes in streptozotocin (STZ)-induced diabetes in neonatal rats, a model of non-insulin- dependent diabetes mellitus (NIDDM). Diabetes mellitus was induced in 28 one day old Sprague-Dawley neonatal rats using a single intrapretoneal injection of STZ (85 mg/kg body weight) freshly dissolved in 0.9% saline solution. Fourteen normal control neonatal rats received an equivalent volume of 0.9% saline solution alone. Twelve weeks after the induction of diabetes, seven of the untreated- normal control rats (NC/12) and seven of the diabetic control rats (nSTZ/12) were randomly selected and sacrificed. Twenty-eight remaining diabetic animals were randomly allocated to three groups of seven animals each. The treated groups were as follows: the nSTZ/16 diabetic control group (STZ-injected neonatal rats), the nSTZ/M group (STZ-injected neonatal rats treated with 20 mg/kg MC fruit aqueous extract twice a day), and the nSTZ/G group (STZ injected neonatal rats treated with 0.1 mg/kg glibenclamide twice a day). Meanwhile, the non-diabetic rats were considered as a normal control group (NC/16). At the end of four weeks treatment period, all these experimental animals were sacrificed. All biochemical evaluations and histopathological examinations were carried out before treatment (12 weeks after diabetes induction) and 4 weeks post-treatment (16 weeks after diabetes induction). Blood samples were collected to measure blood glucose and serum insulin level. Intraperitoneal glucose tolerance test (IPGTT) and intraperitoneal insulin tolerance test (IPITT) were also performed. Serum alanine aminoteransferase (ALT) and aspartate aminoterasferase (AST) were measured. Measurements of serum urea and creatinine were performed. Urine creatinine, urine total protein and glomerular filtration rate (GFR) were determined. Determination of malondialdehyde (MDA) profile of selected tissues (plasma, pancreas, liver, and kidney) was also carried out. Upon euthanasia of experimental animals, the pancreas, liver, and kidney specimens were removed and processed for light microscopy, electron microscopy examination, and immunohistochemical study. The results obtained from the effect of the Me fruit extract showed significant decrease in blood glucose (P<O.05)and increase in insulin level (P<O.05)in the treated groups (nSTZjM and nSTZjG) compared to the diabetic groups. The results also showed that the Me fruit extract and glibenclamide improved glucose tolerance and increased insulin sensitivity in the treated diabetic rats. Serum ALT and AST levels significantly (P<O.05)decreased in the treated diabetic rats. Administration of the Me fruit extract and glibenclamide also significantly (P<O.05)improved GFR, urine total protein, serum creatinine and urea in the treated diabetic rats. The MDA levels in the pancreas, liver, renal tissues and plasma were markedly (P<O.05)lower in the nSTZjM than those of the diabetic rats. Histopathological examination showed that Me fruit extract and glibenclamide significantly (P<O.05)alleviated damages induced by diabetes in the pancreas, liver, and kidney of treated diabetic rats. It also exhibited that the number of insulin positive ~-cells significantly (P<O.05)increased in the nSTZjM rats in comparison with diabetic rats. In conclusion, the results of the current investigation indicate that the aqueous extract of MC fruit was effective in improving the pancreatic, hepatic, and renal functions in the treated diabetic rats. Furthermore, administration of the MC fruit extract also alleviated the damage induced by diabetes in the pancreas, liver, and kidney of treated diabetic rats.